Nutritional Status and Dietary Practices of Elderly People Living In Community Dwelling and Old Age Home In Tanahun District, Nepal - Dhakal, Dijson; Yadav, Dipendra Kumar; Pokhrel, Amritraj; Banstola, Binayak; Koirala, Monika (Clinical Medicine And Health Research Journal, 2023)
Background: The main objective of the study was to access the nutritional status and dietary practice of elderly population living in community dwelling and old age home of Tanahun district, Nepal. Methods: Community-based cross-sectional comparative study was conducted in Tanahun district. The Mini-Nutritional Assessment tool was used to investigate the nutritional status and dietary practices. It was identified by using weekly food consumption and 24 hours dietary recall questionnaires. Data were entered in Epi-Data (version 3.1) and analyzed by SPSS (version 20). Result: Among 202 respondents (101 each from community dwellings and old age home), 44.5% were at risk of malnutrition, 5.9% were malnourished and 49.5% had normal nutrition status in community dwelling. Similarly, 55.4% were at risk of malnutrition, 17.8% were malnourished and 26.7% had normal nutrition status in old age home. In both settings, consumption of protein is low and consumption of vegetables is high. There was a significant association between socio-demographic variables such as living settings, age and education with nutritional status of elderly population. Age (AOR =0.0.186, p= 0.01) and education (AOR = 5.419, p= 0.006) shows significant association with nutritional status. Conclusion: Overall half of them were at risk of malnutrition in both settings due to poor dietary practices, loss of appetite, weight loss, morbidity, neuropsychological problems among senior people. Cardinal focus should be given to improve the consumption of protein in dietary practices. Further longitudinal research studies should be conducted to determine factor associated with malnutrition to prevent malnutrition at regional and national level.